Hell gate - Fairstein, Linda A. (New York : Dutton, 2010)
Alexandra Cooper, a Manhattan assistant district attorney, discovers a link between the wreck of a ship carrying human cargo and a sex scandal involving a promising New York congressman.
Keywords: Cooper, Alexandra (Fictitious character) -- Fiction; Public prosecutors -- Fiction; Human trafficking -- Fiction; Women lawyers -- Fiction; New York (N.Y.) -- Fiction; Mystery fiction; Legal stories